Effect of a transition section between the Blumlein line and a load on the output voltage of gigawatt intense electron-beam accelerators - Xin-Bing Cheng; Jin-Liang Liu; Yu Zhang; Jia-Huai Feng; Bao-Liang Qian (Physical Review Special Topics. Accelerators and Beams, 2009)
The flat voltage of the main pulse on the load of intense electron-beam accelerators (IEBA) is one of the important factors which affect the quality and characteristic of the output beam current of IEBA. In this paper, the effect of the transition section between the Blumlein pulse forming line (BPFL) and load on the output voltage of IEBA is analyzed in theory. Based on the telegraph equations of the BPFL, a formula which is used to calculate the output voltage of IEBA is obtained, and the factor which affects the output voltage is analyzed. It is found from the theoretical analysis that the wave impedance and transmission time of the transition section influence considerably the fluctuation of the main pulse voltage waveform at the load. In order to get a well-shaped square waveform at load and to improve the electron-beam quality of such an accelerator, there should be a proper wave impedance of the transition section, and the transmission time of the transition section should be designed as short as possible. At last, some experiments are performed on IEBA, and the experimental results show reasonable agreement with theoretical analysis.